2001
DOI: 10.1097/00006982-200106000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Erosion and Intrusion of Silicone Rubber Scleral Buckle

Abstract: Erosion and intrusion of scleral buckle are rare complications of scleral buckling procedures. The intruding buckle may be left intact unless there is significant threat to the integrity of ocular structures, recurrent detachment, or hemorrhage. Manipulation of the encircling band or buckle does not necessarily alter the visual acuity or the status of the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 9 publications
0
40
0
8
Order By: Relevance
“…Rarely, SBs can be associated with complications and require removal in 1% to 24% of cases. [1][2][3][4][5][6][7][8][9] Reported indications for SB removal are numerous and include SB exposure, SB extrusion, migration of SB elements, [4][5][6][7][8][9][10][11][12][13][14][15] intrusion of SB, 13,[16][17][18][19][20] infection, 2,6-8,10,13 chronic pain, inflammation, foreign body sensation, 3,6,7,9,13,14,21 strabismus and diplopia, [6][7][8][9]10,11,14,21 recurrent subconjunctival hemorrhage, 3 macular distortion, 3 impingement of the optic nerve, 3 swelling of buckle elements, 11,21 granuloma, 10,11 sudden loss of vision, …”
Section: Introductionmentioning
confidence: 99%
“…Rarely, SBs can be associated with complications and require removal in 1% to 24% of cases. [1][2][3][4][5][6][7][8][9] Reported indications for SB removal are numerous and include SB exposure, SB extrusion, migration of SB elements, [4][5][6][7][8][9][10][11][12][13][14][15] intrusion of SB, 13,[16][17][18][19][20] infection, 2,6-8,10,13 chronic pain, inflammation, foreign body sensation, 3,6,7,9,13,14,21 strabismus and diplopia, [6][7][8][9]10,11,14,21 recurrent subconjunctival hemorrhage, 3 macular distortion, 3 impingement of the optic nerve, 3 swelling of buckle elements, 11,21 granuloma, 10,11 sudden loss of vision, …”
Section: Introductionmentioning
confidence: 99%
“…Reported rates of intraoperative scleral perforation reach 8% for silicone buckles and range from 0 to 18% for MIRAgel explants. 10,20,[24][25][26] Crama and Klevering 27 in their study of 467 MIRAgel cases reported 11% of intraoperative scleral perforation or RR. The presence of an active ocular infection (cultures were not reported) and a history of more than one preceding RD procedures were significantly associated in their report with a higher risk of scleral perforation during the removal procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In episcleral implants the capsule seals off the buckle, thereby helping to minimize the risk of later infection. As regards intrascleral implants, the capsule also grows between the implant and sclera, thereby giving further protection against scleral erosion [70]. Because dense silicone does not allow tissue in-growth, the implant can easily be taken out in one piece without too much trauma, if removal becomes necessary [71,72].…”
Section: Routinely Used Implants In Clinical Practicementioning
confidence: 99%
“…Today, silicone is considered by surgeons as the -gold standard‖ material for manufacturing scleral buckles [69][70][71][72][73][74][75] and solid/porous silicone implants are marketed worldwide. More than seventy style options for silicone buckles are currently available to the ophthalmic surgeons seeking an implant designed to achieve a particular width, height or shape of the buckle.…”
Section: Summary Of Current Solutionsmentioning
confidence: 99%